UNDERSTANDING USERS’ SWITCHING INTENTION ON MOBILE WALLET - Lim Kah Boon; Yeo Sook Fern; Tan Choon Ching (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
In the current era, mobile devices playing an important role in our part of daily life. With today’s technology, users of mobile devices can now use their mobile device to make a payment or transaction instead of using a physical card. A mobile wallet is a way to display your card information in a digital format on your mobile device. As a result, mobile wallets are now growing rapidly in Malaysia and many mobile wallet service providers are available on the current market. For this reason, several issues have been raised in this research in order to study the factors that affect users ’ intention to switch to mobile wallets. The main objective of this research is to examine the factors which affect users’ switching intention on the mobile wallet. A set of self-administered questionnaires has been randomly distributed to 220 respondents for the purpose of data collection. After we had collected all the data from the respondents, data were keyed into Statistical Package for the Social Sciences (SPSS) Version 26 and Smart PLS is used to assess the measurement model and the structural equation model. The data analysis result showed that dissatisfaction, alternative attractiveness, and the subjective norm has a significant relationship towards users’ switching intention on the mobile wallet. Moreover, the service provider should keep improving their service quality to avoid users switching to another one. Lastly, the service provider must keep updating their features or attractiveness, so the users won’t be so easy to switch to another one and influence by other people.